Biocompatibility and osteointegrative characteristics of zirconium ceramic implants for diaphyseal defect filling - Elena A. Volokitina; Maksim V. Saushkin; Irina P. Antropova; Sergey M. Kutepov; Svetlana A. Brilliant (Гений oртопедии, 2025)
Introduction The development of new ceramic materials with high osteointegrative characteristics and experimental substantiation of their application is an important issue in traumatology. The purpose of the work was to study the biological compatibility and osteointegrative characteristics of implants made of zirconium ceramics stabilized with yttrium, ytterbium and gadolinium for filling diaphyseal bone defects in an experiment. Material and methods The study was performed on 18 male Chinchilla rabbits. Diaphyseal defects with intramedullary implantation of a rod made of a new ceramic porous (PC), non-porous (NPC) material and titanium alloy (TA) were modelled. The animals were divided into 3 groups based on the rod used: PC, NPC and TA (n = 6 in each). Hematological parameters were studied one day before and 8 weeks after the operation. Withdrawal of animals from the experiment, X-ray control and tissue sampling with subsequent histological and morphometric examination were performed at 8 weeks after the operation. Statistical data processing was performed using the Statistica 10 software. The Kruskal – Wallis test with subsequent intergroup analysis was used to compare the study groups. The Wilcoxon criterion was used to assess changes in dynamics in individual groups. The results are presented as median and interquartile range. Results Eight weeks after the surgery, in the PC group compared to the NPC and TA groups the levels of leukocytes, monocytes and granulocytes were significantly lower (p = 0.025; p = 0.022; p = 0.005, respectively); no significant differences were found in other hematological parameters. The results of histomorphological studies showed that better integration of implants was observed when using PC rods compared to TA and NPC implants. The thickness of the bone trabecula in the implantation area was significantly higher in the PC group compared to the TA and NPC groups (86.2 [55.8; 109.9], 56.0 [47.2; 75.9] and 33.1 [19.0; 84.5], respectively, in both cases p < 0.001). Discussion We studied the biocompatibility and osteointegrative properties of implants made of a new ceramic material in two versions, nonporous and porous (pore size of 10–50 μm), and compared them with titanium alloy implants. It was previously proven that alloyed ceramic materials are attractive for tissue regeneration due to their functional properties, biological activity, and therapeutic effects provided by the introduced ions. The results of our histological and morphometric studies confirmed the better biocompatibility and osteointegration of implants made of porous zirconium ceramics (PC) containing yttrium, ytterbium, and gadolinium ions, compared to implants made of NPC and TA. Conclusion A new zirconium-based ceramic demonstrates biological compatibility. Implants with pore sizes of 10–50 μm have good osteointegrative characteristics which determine their possible use in the treatment of bone defects.